Does personality always matter for health? Examining the moderating effect of age on the personality-health link from life span developmental and aging perspectives - Luo, Jing; Zhang, Bo; Graham, Eileen K; Mroczek, Daniel K (My University, 2023)
Extensive evidence has been found for the associations between personality traits and health. However, it remains unknown whether the relationships between personality and health show differential patterns across different life stages. The current research examined how the associations between the levels of and changes in the Big Five personality traits and different types of health outcomes (self-rated, physical, and physiological health outcomes) differ across ages over the life span (Sample 1, age range: 15-100) and during the aging process (Sample 2, age range: 50-109) in particular. Using data from the two large longitudinal studies-the Household, Income, and Labor Dynamics in Australia Survey and the Health and Retirement Study, we observed three important patterns. First, levels of and changes in personality traits were significantly associated with health across different life phases, and these effects were observed even in very old ages. Second, overall, the prospective relations between personality traits/changes in personality traits and health outcomes increased in strength in middle adulthood and/or early stages of late adulthood; however, the strength of their connections diminished in very old ages. Finally, there were some trait-specific and health outcome-specific patterns in the age-differential associations between personality and health. Findings from the present study contribute to enhancing our understanding of the personality-health link from a developmental perspective and provide critical information for the design and implementation of screening and interventions targeting health promotion. (PsycInfo Database Record (c) 2023 APA, all rights reserved).